GAMBARAN PELAKSANAAN PERENCANAAN PASIEN PULANG TERINTEGRASI PADA PASIEN CEREBRAL VASCULAR ACCIDENT (CVA) - Fatimatuzzahra khairunisa (Jurnal Keperawatan GSH, 2024)
Introduction: Patients with Cerebral Vascular Accident (CVA) or stroke have physical, psychological, social and economic impacts. So the daily activities of stroke patients require help and support from other people, especially when the patient is discharged from the hospital. Nurses play a very important role in planning a patient's discharge, including education and care carried out after the patient leaves the hospital. Planning for patients to go home can improve the interpersonal teaching and learning process, nurses play a role in explaining the nursing actions received by patients. Method: This research uses a qualitative descriptive method, with a total sample sampling technique of 15 nurses in the stroke ward, data collected by direct observation. The analysis used is descriptive analysis to determine the frequency distribution of variable categories, namely data for evaluating the implementation of patient discharge planning. Results: Introduction education was 100% implemented, 73% regulations were implemented well, disease/diagnosis education was 100% implemented well. Implementation of education during treatment was 100% carried out. Education with METHOD, implementation of Medication education is 100%, Environmental education with 13% category is well implemented, Treatment education with 26% is well implemented. Health education is 100% well implemented, Outpatient referral education is 100% good, Diet education is 100% well implemented. Conclusion: Nurses as discharge planners are in a good category in providing education when admitted to hospital and when patients are treated, but there are nurses who have not provided education when patients go home using METHOD (Medication, Environment, Treatment, Health, Outpatient referral, Diet).   Pendahuluan : Pasien dengan Cerebral Vascular Accident (CVA) atau stroke memiliki dampak baik fisik, psikologis, social dan ekonomi. Sehingga aktifitas sehari hari pasien stroke memerlukan bantuan dan dukungan dari orang lain, terutama  pada saat keadaan pasien setelah keluar rumah sakit. Perawat sangat berperan penting dalam perencanaan pulang pasien meliputi edukasi serta perawatan yang dilakukan setelah pasien keluar rumah sakit. Perencanaan pasien pulang dapat meningkatkan proses belajar mengajar interpersonal, perawat berperan dalam menjelaskan tindakan keperawatan yang diterima pasien. Metode : Penelitian ini menggunakan metode deskriptif kualitatif, dengan Teknik sampling total sample yaitu 15 perawat yang berada di bangsal stroke, data yang dikumpulkan dengan cara observasi langsung. Analisa yang digunakan adalah Analisa deskriptif untuk mengetahui distribusi frekuensi kategori  variable yaitu data untuk evaluasi pelaksanaan perencanaan pemulangan pasien. Hasil : Edukasi pengenalan 100% terlaksana, peraturan 73% terlaksanan dengan baik, edukasi penyakit/diagnosa 100% terlaksanan baik. Pelaksanaan edukasi selama dirawat 100% terlaksana. Edukasi dengan METHOD, pelaksanaan edukasi Medication yaitu 100%, edukasi Environtment dengan kategori 13% terlaksana dengan baik, edukasi Treatment dengan 26% terlaksana dengan baik. edukasi Health dengan 100% terlaksana dengan baik, edukasi Outpatient referral dengan kategori baik 100%, edukasi Diet dengan kategori 100% terlaksana dengan baik. Kesimpulan : Perawat sebagai perencana pemulangan sudah dalam kategori baik dalam memberikan edukasi saat masuk rumah sakit dan saat pasien dirawat, namun terdapat perawat yang belum melakukan edukasi saat pasien pulang dengan METHOD (Medication, Environtment, Treatment, Health, Outpatient referral, Diet).